STUDI ANALISIS LATAR BELAKANG PENDIDIKAN, SERTIFIKASI GURU DAN USIA GURU PAUD DI KOTA BANDAR LAMPUNG BERDASARKAN HASIL NILAI UJI KOMPETENSI GURU (UKG) - Qomario, Qomario; Kurniasih, Siti; Anggraini, Hetty (Jurnal Caksana : Pendidikan Anak Usia Dini, 2018)
The competence of PAUD teachers is indispensable in achieving early childhood education goals, in fact 47.42% of PAUD teachers have not obtained UKG scores according to the criteria or can be said to have no professional and pedagogic competence in the high category. Therefore, it is necessary to study the education background, certification, and age of PAUD teachers towards the UKG results. The purpose of the study was to analyze: (1) the achievement of the value of UKG for Early Childhood Education (PAUD) teachers in Bandar Lampung in 2015, (2) educational background, certification, and age of PAUD teachers who had attended UKG in Bandar Lampung City in 2015. The results of the research were found: (1) Competency mapping based on educational background, certification, and age of PAUD teachers and (2) Formulation of recommendations of policy makers on the effectiveness of programs in improving the competence of PAUD teachers in the form of education and training, seminars, internships, workshops, and comparative studies to support PAUD teacher professionalism. Keywords: Test of Teacher Competence, PAUD Teacher Certification, Educational Background, Age of PAUD Teachers